Yerba mate (Ilex paraguariensis A. St. – hil.): a comprehensive review on chemical composition, health benefits and recent advances (Research, Society and Development, 2021)
Chimarrão is a typical drink from the southern region of Brazil and produced from the leaves and branches of Ilex paraguariensis that will form the yerba mate. The purpose of this review is to provide a concise summary of research published in the last 10 years with an emphasis on the Ilex paraguariensis species, its general characteristics, chemical composition and its main health benefits. This study is an exploratory descriptive literature review regarding the biological activity and pharmacological action of the plant Ilex paraguariensis A. St. - Hill. The Scientific Electronic Library Online (Scielo), National Library of Medicine (Pubmed), Scopus and Academic Google databases were used for research. The main chemical compounds identified in the yerba mate extract are: polyphenols (chlorogenic acid) and xanthines (caffeine and theobromine). Among the potentially beneficial effects on human health are activities such as: antioxidant, anti-inflammatory, antimicrobial, anti-obesity, anti-diabetic, neuroprotective, cardiovascular protection, regulation of the intestinal microbiota and anti-cancer. Therefore, beverages produced from Ilex paraguariensis have great potential as a source of biological compounds for the pharmaceutical and nutraceutical industry.